STUNTING PREVENTION WITH CONTENTS OF "ISI PIRINGKU" IN DAGEN HAMLET, POLOKARTO DISTRICT: PENCEGAHAN STUNTING DENGAN "ISI PIRINGKU" DI DUSUN DAGEN KECAMATAN POLOKARTO - Ayudia Johar, Syefira; Sartika, Iik (Darmabakti Cendekia: Journal of Community Service and Engagements, 2024)
Background: According to SSGI data (2019-2021), the risk of stunting can manifest before birth and reaches its peak between 6 months (13.8%) and 12 months (27.2%) of age. Community nutrition interventions, particularly during the first thousand days of life, emphasize the consumption of animal protein to expedite the reduction of stunting. In Sukoharjo Regency, based on simultaneous weighing conducted in 2022, the highest prevalence of stunting cases was recorded in Polokarto District at 13.6%. Government initiatives to combat stunting include programs such as "Isi Piringku". Objective: This study aimed to assess the increase in respondents' knowledge through pre-test and post-test evaluations. Method: This activity comprises three stages: pre-test, implementation, and post-test. Questionnaire data obtained will be analyzed to evaluate the effectiveness of knowledge transfer. Results: Overall, there was a 42.61% increase in knowledgerelated outcomes following the service intervention. The attendance target for service activities was achieved, with 80% participation from all participants. Conclusion: The implementation of the service intervention has provided significant benefits for mothers of toddlers attending Posyandu programs and is anticipated to be sustained in the long term.